2019
DOI: 10.18203/2320-1770.ijrcog20190276
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum neutrophil gelatinase associated lipocalin (NGAL) levels with preeclampsia

Abstract: Background: Preeclampsia is a systemic disorder that affects multiple organs and is characterized by the new onset of hypertension and proteinuria or end-organ dysfunction or both in the second half of pregnancy. NGAL is a 25-KDa protein of the lipocalin family and is considered to be a novel biomarker for ischemic injury. The objective of this study is to compare the levels of serum NGAL in preeclamptic patients and gestational age matched normotensive controls.Methods: The study design is case control study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…In contrast, Ahmad et al (21) found a non-significant difference between the PE and control groups, but the sample size in this study was small. The same results were shown by Dhivya (22) study where nothing was mentioned about the severity of the disease.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, Ahmad et al (21) found a non-significant difference between the PE and control groups, but the sample size in this study was small. The same results were shown by Dhivya (22) study where nothing was mentioned about the severity of the disease.…”
Section: Discussionsupporting
confidence: 83%